Malaysian Youth Awareness Towards Spiritual Program - Abd. Wahab, Norazlina; Abd. Ghani, Abdullah; Maamor, Selamah; Aziz, Ahmad Bashir; Ahmad Razimi, Mohd Shahril; Nik Abdullah, Nik Safiah; Elias, Nor Hanim (Khalsa Publications, 2018)
The aim of this study is to examine the awareness on spirituality programs among youth in Malaysia. In Islam, spirituality is defined as the presence of a relationship with Allah that affects the individual?s self-worth, sense of meaning, and connectedness with others and nature. It has significant effect for health, positive development of a person?s sense of self and for enabling identity to frame the individual?s pursuit of a life path eventuating in idealized adulthood. The lack of spirituality may leads to social problems such as loitering, racers, bohsia, bohjan, club servers (GRO), alcohol consumption, and drug abuse. To minimize these problems, the government as well as the private sectors manage to setup various programs and activities in order to develop and improve spirituality among youth. Hence, awareness on these programs is imperative. Use of press media, incorporation in mainstream education (basic, secondary and tertiary), celebrities? participation in spirituality programs are some of the ways by which spirituality programs and activities can be heralded. Using a survey of 4703 youth in Malaysia, this study aims to examine the awareness of youth in Malaysia towards the existence of spirituality program for youth. The paper concluded with recommendations of ways of sensitizing youth on the need to be spirituality conscious